2022
DOI: 10.1111/spc3.12709
|View full text |Cite
|
Sign up to set email alerts
|

Self‐esteem development and life events: A review and integrative process framework

Abstract: Self-esteem is a pervasive individual characteristic with major consequences for people's lives. Recent research demonstrated normative change and substantial individual differences in change across the lifespan, which triggered great interest in the sources of self-esteem development. This article provides an overview of the present state of the field of self-esteem development. First, to gain a comprehensive picture, I reviewed findings of different change indicators: mean-level change, individual difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
1
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 161 publications
4
43
1
6
Order By: Relevance
“…Rigorous study designs with dense assessments are needed to capture the individual experience (e.g., sense of mastery) and short-and longer-term change in personality traits and (average) personality states during life transitions (Bleidorn et al, 2018;Reitz, 2022).…”
Section: Methodological Opportunity: Bottom-up Processesmentioning
confidence: 99%
See 3 more Smart Citations
“…Rigorous study designs with dense assessments are needed to capture the individual experience (e.g., sense of mastery) and short-and longer-term change in personality traits and (average) personality states during life transitions (Bleidorn et al, 2018;Reitz, 2022).…”
Section: Methodological Opportunity: Bottom-up Processesmentioning
confidence: 99%
“…For example, the aforementioned study found correlated change in achievement-related daily experience and self-esteem only in those who stared to work. In addition, while our study used more highly dense assessments than most research and still covered 2 years, it was not suited to capture longer-term changes in personality traits, anticipatory change, or micro-level state processes within days or weeks, which should be examined in other studies to obtain a more complete picture of the short-to-long-term change processes (Reitz, 2022;Wrzus & Roberts, 2017).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Self-esteem changes systematically across time, it is relatively stable around its trait level in response to environmental conditions (Reitz, 2022).…”
Section: Nurses' Self-esteemmentioning
confidence: 99%